2017
DOI: 10.1146/annurev-med-052915-015720
|View full text |Cite
|
Sign up to set email alerts
|

Oral Combination Therapies for Hepatitis C Virus Infection: Successes, Challenges, and Unmet Needs

Abstract: The current standard of care for the treatment of hepatitis C virus (HCV) consists of interferon-free direct-acting antiviral (DAA) regimens, including combinations of DAAs and fixed-dose combination pills. DAAs for HCV are likely to be heralded as one of medicine's greatest advancements. Viral eradication rates are pushing 100% for many HCV-infected populations, including patients with HIV/HCV coinfection, decompensated cirrhosis, liver and kidney transplants, and end-stage liver disease. We highlight the gre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
29
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 57 publications
(31 citation statements)
references
References 57 publications
0
29
0
Order By: Relevance
“…In the last 5 years, treatment of chronic hepatitis C virus (HCV) infection has been revolutionized by the development of all‐oral combination regimens of direct‐acting antivirals (DAAs) that have rapidly superseded pegylated interferons (pegIFNs) plus ribavirin (RBV) as the standard of care . These DAA regimens have proven to be better tolerated than pegIFN‐based therapies, with higher rates of posttreatment sustained virologic response (SVR; a surrogate of cure) and shorter treatment durations …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In the last 5 years, treatment of chronic hepatitis C virus (HCV) infection has been revolutionized by the development of all‐oral combination regimens of direct‐acting antivirals (DAAs) that have rapidly superseded pegylated interferons (pegIFNs) plus ribavirin (RBV) as the standard of care . These DAA regimens have proven to be better tolerated than pegIFN‐based therapies, with higher rates of posttreatment sustained virologic response (SVR; a surrogate of cure) and shorter treatment durations …”
mentioning
confidence: 99%
“…1 These DAA regimens have proven to be better tolerated than pegIFN-based therapies, with higher rates of posttreatment sustained virologic response (SVR; a surrogate of cure) and shorter treatment durations. 2,3 Daclatasvir (DCV; tablets) is an orally available small molecule and pangenotypic nonstructural protein (NS) 5A inhibitor with picomolar in vitro activity against HCV genotypes (GT) 1-6 4 ; asunaprevir (ASV; capsules) is also an orally available small molecule and tripeptidic acylsulfonamide inhibitor of the HCV NS3/4A protease with vitro antiviral activity against GTs 1, 4, 5, and 6. 5 In early replicon studies, an additive to synergistic interaction between DCV and ASV was observed.…”
mentioning
confidence: 99%
“…Of the six major hepatitis C virus (HCV) genotypes, infection with genotype 1 is the most prevalent, accounting for nearly half of all HCV infections worldwide . A paradigm shift in the treatment of patients with chronic HCV genotype 1 infection occurred in 2011 with the introduction of direct‐acting antivirals (DAAs), which interfere with HCV replication by targeting viral proteins such as the nonstructural protein (NS) 3/4A serine protease, NS5A, and the polymerase, NS5B . For the few patients with genotype 1 infection who fail interferon (IFN)‐free DAA‐based therapies, retreatment strategies remain unclear.…”
mentioning
confidence: 99%
“…In the last 5 years, treatment of chronic hepatitis C virus (HCV) infection has been revolutionized by the development of all‐oral combination regimens of direct‐acting antivirals (DAAs) that have rapidly superseded pegylated interferons (pegIFNs) plus ribavirin (RBV) as the standard of care . These DAA regimens have proven to be better tolerated than pegIFN‐based therapies, with higher rates of posttreatment sustained virologic response (SVR; a surrogate of cure) and shorter treatment durations . Although the all‐oral combination therapy of daclatasvir and asunaprevir had been approved as the first direct‐acting antiviral therapy (DUAL treatment) in Japan, not requiring injectable pegIFN or RBV, for treating genotype‐1 (GT 1), still there were difficult‐to‐treat patients including GT 1 patients especially who have NS5A mutation.…”
mentioning
confidence: 99%
“…[1][2][3] These DAA regimens have proven to be better tolerated than pegIFN-based therapies, with higher rates of posttreatment sustained virologic response (SVR; a surrogate of cure) and shorter treatment durations. 4,5 Although the all-oral combination therapy of daclatasvir and asunaprevir had been approved as the first direct-acting antiviral therapy (DUAL treatment) in Japan, not requiring injectable pegIFN or RBV, for treating genotype-1 (GT 1), still there were difficult-to-treat patients including GT 1 patients especially who have NS5A mutation. NS5A amino acid polymorphisms L31M/V and Y93H have been identified as the major pretreatment HCV resistance-associated substitution to daclatasvir in GT 1b and have been observed to reduce the efficacy of DUAL treatment when present at baseline.…”
mentioning
confidence: 99%